Energy use categorization with performance indicators for the food industry and a conceptual energy planning framework. (15th December 2021) - Kanchiralla, Fayas Malik; Jalo, Noor; Thollander, Patrik; Andersson, Maria; Johnsson, Simon
Highlights: A novel taxonomy for the monitorization of energy use in the food industry. Energy end use and CO2 emissions analysis based on the suggested taxonomy. Potential energy performance indicators are suggested for the food industry. A novel energy planning framework in an industrial context is suggested. Abstract: Energy efficiency improvements can enhance industry's decarbonization. A major challenge however is that the energy efficiency potential often remains untapped, due, among other things, to the lack of information on energy end-use and available energy efficiency measures. Further, this lack of information also makes the deployment of energy efficiency difficult to monitor and evaluate. The creation of a standard or taxonomy on how to categorize energy end-use for major industries would help to close this knowledge gap. This paper presents a novel taxonomy for energy end-use in the food industry, with four hierarchical levels. Further, results show that the production process utilizes two-thirds of the total energy used in the food industry and only one-third is used for support processes. Another result is that heat processing and space heating are the most intensive unit processes in terms of energy and carbon dioxide emissions for production and support processes, respectively. The paper also presents an array of energy performance indicators for the identified energy-intensive processes. The case study was carried out in the Swedish food industry. However, taxonomy and energy performance indicators can be generalized internationally. In addition to the above results, this research presents a novel concept of the energy planning framework, which helps with simple and effective planning of energy improvement activities in an industrial context. The energy planning framework can help in benchmarking, setting targets, and monitoring energy performance in the industry.